2018
DOI: 10.3390/ijms19092801
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NOS2 Activity on Human Glioma Cell Growth, Clonogenic Potential, and Neurosphere Generation

Abstract: Aberrant nitric oxide synthase 2 (NOS2) expression has been suggested as an interesting therapeutic target that is being implicated as a component of the molecular profile of several human malignant tumors, including glioblastoma, which is the most aggressive brain tumor with limited therapeutic options and poor prognosis. The aim of the present work was to evaluate the effect of 1400W, a specific NOS2 inhibitor, on human glioma cells in terms of clonogenic potential, proliferation, migration rate, and neurosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 62 publications
(80 reference statements)
4
25
0
Order By: Relevance
“…Recently, it was reported that 1400 W significantly reduces the proliferation, migration, colony formation, and neurosphere generation ability in U‐87 MG and T98G glioma cell lines, as well as in the human glioma primary cells. This study sustains the emerging relevance of iNOS as a prognostic factor of glioma malignancy and recurrence, supporting the potential therapeutic value of safer iNOS inhibitors for a better management of this cancer …”
Section: Small Molecules Able To Downregulate Inos As Antiglioma Agentssupporting
confidence: 77%
“…Recently, it was reported that 1400 W significantly reduces the proliferation, migration, colony formation, and neurosphere generation ability in U‐87 MG and T98G glioma cell lines, as well as in the human glioma primary cells. This study sustains the emerging relevance of iNOS as a prognostic factor of glioma malignancy and recurrence, supporting the potential therapeutic value of safer iNOS inhibitors for a better management of this cancer …”
Section: Small Molecules Able To Downregulate Inos As Antiglioma Agentssupporting
confidence: 77%
“…Mixed (in vitro and in vivo in both human and mouse) Glioma cells, GSCs and blood samples [18,41] IL-6 and IL-8 partially mediated by glioma cells have a protective effect on blood neutrophils In vitro human Blood neutrophils and glioma cells [46] Depletion of neutrophils via monoclonal antibody against Ly6G prolongs the survival of mice with developing gliomas Mixed (in vitro and in vivo in mouse, and in vitro human) Transgenic mice and patients' blood [47] TANs are associated with tumor aggressiveness in mutant-IDH1 glioma Mixed (in vivo mouse and human) Transgenic mice, patients tumor tissue and blood cells/RNA [21] Primary glioma cells sustaining NOS2 activity promote proliferation, migration, and neurosphere generation and represent a prognostic factor for glioma malignancy and recurrence Human in vitro Glioma cell lines and primary culture [48] Radiation-induced infiltrating Ly6G+ neutrophils support the conversion of GBM tumor cells to GSCs via the regulation of nitrosative stress and dedifferentiation (NOS2-NO-ID4) signaling in newly diagnosed/recurrent GBM patients, and this is negatively associated with survival and radiation therapy outcomes Mixed (in vitro and in vivo in both human and mouse)…”
Section: Mixed (In Vitro and In Vivo In Both Human And Mouse)mentioning
confidence: 99%
“…Recently, it has been reported that radiation-induced senescence in GBM cells promotes the recruitment of Ly6G + (TANs) and modulates tumor microenvironmental cells and vessel formation through nuclear factor kappa-light-chain-enhancer of activated B cell (NFκB) signaling [49,67]. Palumbo et al showed that infiltrating Ly6G + cells support the conversion of GBM tumor cells to a more stem-like state through dedifferentiation and nitrosative stress (NOS2-NO-ID4) signaling [48]. Jeon et al further confirmed this mechanism by showing that NFκB inhibitors and Ly6G-neutralizing antibodies reduced the number of GSCs and prolonged the survival of tumor-bearing mice after RT [49].…”
Section: Rt Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Expression of iNOS is a hallmark of chemoresistance in gliomas (brain tumors). Several studies have reported that inhibition of iNOS could be related to a decrease in proliferation of glioma cells . Based on this correlation between iNOS and gliomas, the same research group developed anti‐glioma agents by appending natural amino acids on the free –NH 2 group of 6 .…”
Section: Synthetic Inos Inhibitorsmentioning
confidence: 99%